Human anatomy - Van De Graaff, Kent M. (McGraw-Hill, 2000)
In this comprehensive text, the human body is presented in full-colour and is explained in understandable terms. This edition continues to provide a basic introduction to the structure, function and possible dysfunction of the human body and includes illustrations and clinical case studies.